CSR Disclosure, Foreign Ownership, and Tax Aggressiveness: Evidence from Indonesian Mining Companies toward SDG 16 - Abidah Dwi Rahmi Satiti; Doddy Setiawan; Djoko Suhardjanto; Wahyu Widarjo; Setianingtyas Honggowati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To examine the effect of corporate social responsibility disclosure on tax aggressiveness and investigates whether foreign ownership moderates this relationship among mining companies listed on the Indonesia Stock Exchange. This study contributes to Sustainable Development Goal (SDG) 16 by highlighting the importance of transparency, accountability, and responsible corporate governance in taxation practices. Method: The quantitative study uses secondary data from annual reports and financial statements of mining companies listed on the Indonesia Stock Exchange during 2015–2019. Using purposive sampling, this study obtained 135 firm-year observations. Tax aggressiveness was measured using the effective tax rate (ETR), CSR disclosure was measured using the GRI-G4 based CSR Disclosure Index, and foreign ownership was measured based on the proportion of shares owned by foreign investors. Moderated regression analysis was conducted using STATA. Results: The results indicate that CSR disclosure has a significant effect on tax aggressiveness. Companies with higher CSR disclosure tend to demonstrate greater tax aggressiveness. However, foreign ownership does not significantly moderate the relationship between CSR disclosure and tax aggressiveness. Novelty: Providing new evidence regarding the role of foreign ownership as a moderating mechanism between CSR disclosure and tax aggressiveness in an emerging market mining sector. The findings emphasize that CSR disclosure should reflect genuine corporate accountability rather than merely symbolic legitimacy, supporting SDG 16.6 through improved transparency and responsible institutional practices.